Tau and apolipoprotein E modulate cerebrovascular tight junction integrity independent of cerebral amyloid angiopathy in Alzheimer's disease. Issue 10 (22nd August 2020) - Liu, Chia‐Chen; Yamazaki, Yu; Heckman, Michael G.; Martens, Yuka A.; Jia, Lin; Yamazaki, Akari; Diehl, Nancy N.; Zhao, Jing; Zhao, Na; DeTure, Michael; Davis, Mary D.; Felton, Lindsey M.; et al.
Abstract: Introduction: Cerebrovascular pathologies including cerebral amyloid angiopathy (CAA) and blood‐brain barrier (BBB) dysregulation are prominent features in the majority of Alzheimer's disease (AD) cases. Methods: We performed neuropathologic and biochemical studies on a large, neuropathologically confirmed human AD cohort (N = 469). Amounts of endothelial tight junction proteins claudin‐5 (CLDN5) and occludin (OCLN), and major AD‐related molecules (amyloid beta [Aβ40], Aβ42, tau, p‐tau, and apolipoprotein E) in the temporal cortex were assessed by ELISA. Results: Higher levels of soluble tau, insoluble p‐tau, and apolipoprotein E (apoE) were independently correlated with lower levels of endothelial tight junction proteins CLDN5 and OCLN in AD brains. Although high Aβ40 levels, APOE ε4, and male sex were predominantly associated with exacerbated CAA severity, those factors did not influence tight junction protein levels. Discussion: Refining the molecular mechanisms connecting tau, Aβ, and apoE with cerebrovascular pathologies is critical for greater understanding of AD pathogenesis and establishing effective therapeutic interventions for the disease.